Discriminant analysis in the assessment of functional and motor preparedness of high school girls - Худолій, О. М.; Іващенко, О. В. (Physical Education Theory and Methodology, 2014)
The aim — to define methodological approaches to teaching motor control and functional readiness of high school girls. Research methods. To achieve the objectives adopted the following methods: analysis of scientific literature, teaching and testing methods of mathematical statistics. To evaluate the functional and physical fitness of girls grades 9—11 trial results registered post, Ghencea, Serkina and motor tests. In the study involved girls in grade 9 — 24 persons, 10 class — 21 people, 11 class — 26 people. Results. Standardized canonical discriminant function coefficients can determine the value contribution of variables in the function result. With the largest contribution to the canonical function of one variable are 3, 4 and 7: the higher the value of these variables, the more important functions. With the largest contribution to the canonical function of two variables are 1, 8 and 5: The higher the value of these variables, the more important functions. The first function is to explain 96.9% variance of results, the second — by 3.1%. The foregoing demonstrates the possibility of classifying differences in age girls grades 9—11 based functional testing, power and coordination training. Structural canonical discriminant function coefficients indicate that it is most significantly associated with the number 9, 7 and 6 variables: thus a significant difference between girls grades 9—11 there in the samples Serkina, weights, speed force. Conclusions. For the final pedagogical control motor and functional training girls grades 9—11 can be used first discriminant function with an emphasis on the most informative variables.